Embracement in urgency/emergency and relationships in nursing care - Lopes, Viviane Costa; Ascari, Bruna; Santarem, Michelle Dornelles; Chassot, Maicon Daniel; Machado, Elisiane de Oliveira; Vizini, Simone Thais; Santos, Suimara; Inchauspe, Juciane A. Furlan; Machado, Raquel Adjane; Michelin, Fabiano da Costa (Seven Editora, 2024)
The objective of this paper is to review on the reception by nurses working in emergency rooms, through papers and literature published between 2000 and 2010. for both the methodological approach is an exploratory descriptive qualitative approach, aimed to describe and develop as a review of the literature in the context of reception of the users by nurses working in the area at emergency. The methodological design for this study was the literature search. We tried to base the database of journals in the VHL (Virtual Health Library): focusing on the following databases: Lilacs (the Latin American and Caribbean Center on Health Sciences Information), SciELO (Scientific eletronics library online) and BEDENF (Database of Nursing), using the keywords: nursing in emergency care, care in emergency rooms, humane nursing. Following the established inclusion criteria, such as full texts in English in the period 2000 to 2010 and emphasizing the protection of users by nurses working in the area of emergency care, we selected 25 articles. The results showed that the inter-demands-care needs of emergency services and emergency services are quite complex, since it depends largely on the health, among other factors, quality of life, how to characterize it, the cultural translation of health and disease and healing, the profile of social protection in this sector and modes of attention directed to built and human needs. In this scenario, it behooves the nursing process to accommodate the customer in emergency rooms, looking for a more efficient screening and qualifying, where the professional can establish through this unique service, the actual need of the patient. DOI:https://doi.org/10.56238/sevened2023.007-067